Anxiety, depression and stress among medical students in Malaysia during COVID-19: a cross-sectional study - Ching, Siew Mooi; Salim, Hani; Lee, Kai Wei; Mohamad, Fadzilah; Ismail, Irmi Zarina; Jafri, Malissa Syahira; Balasingam, Thanesh; Sharizal, Aqilah; Ng, Jun Ying; Tan, Ngiap Chuan (Faculty of Medicine and Health Science, Universiti Putra Malaysia, 2023)
Introduction: This study aimed to determine the prevalence and factors associated with psychological distress following the COVID-19 pandemic among medical students at one of the public universities in Malaysia. Method: From August to October 2020, a web-based cross-sectional study was conducted among undergraduate medical students at a public university. DASS-21, Brief Resilience Scale and WHOQOL-Bref questionnaires were used in this study. Results: The prevalence of depression was 40.5%, anxiety 46.0% and stress 30.9%. Based on multivariate logistic regression, a higher quality of life score is associated with a lower likelihood of depression (AOR=0.583, p<0.001), anxiety (AOR=0.726, p<0.001), and stress, (AOR=0.702, p<0.001) respectively. Likewise, a higher resilience score is less likely to be associated with depression (AOR=0.880, p=0.002), anxiety (AOR=0.880, p=0.002), and stress (AOR=0.850, p<0.001). Older age (OR=0.700, p=0.020) was associated with less stress and being on campus (OR=3.436, p=0.021) was at risk of stress during the COVID-19 pandemic. Conclusion: Our results suggest that medical students with higher quality of life and resilience scores had less depression, anxiety and stress. Older age was associated with less stress, and during the COVID-19 pandemic, being on campus was at risk of stress. Various stakeholders need to keep these findings in mind and identify those who are at risk for developing depression, anxiety, and stress in order to take further action to improve their quality of life and resilience.